OPTIMIZATION OF PHENOLIC COMPOUNDS EXTRACTION FROM PURPLE BASIL LEAF BY CONVENTIONAL AND MICROWAVE ASSISTED EXTRACTION METHODS - Ozcan, B. E.; Sagdic, O.; Karasu, S.; Ozkan, K.; Akcicek, A. (PLAPIQUI(UNS-CONICET), 2021)
The present study aimed to determine the optimum extraction conditions of conventional solvent extraction (CSE) and microwave-assisted extraction (MAE) techniques to obtain maximum total phenolic (TPC), total flavonoid (TFC), total anthocyanin (TAC) and antioxidant capacity (AA). Response surface methodology (RSM) and central composite design (CCD) were used to determine optimum points of CSE and MAE. Both two extraction methods, all parameters significantly affected TPC, AA, TFC and TAC (p<0.05). MAE showed higher bioactive compounds yield than that of CSE. Optimum point for CSE and MAE was found to be 60 degrees C and 30 min and 591.83 W and 2.98 min respectively. TPC, AA, TFC and TAC were obtained as 33.81mg/g, 160.27 mg/g, 11.89 mg/g and 331.01 mg/kg for CSE and 62.99 mg/g, 214.62 mg/g, 21.80 mg/g and 3462.93 mg/kg for MAE respectively. This study recommended that the MAE should be used for the extraction of PBL to increase phenolic extraction yield.
Keywords: Extraction; response surface methodology; phenolic compounds; purple basil; Ocimum basilicum L; BIOACTIVE COMPOUNDS; ANTIOXIDANTS; FLAVONOIDS; LEAVES; YIELD; OIL; Engineering